Learning About Healthy Food Through the Pancasila Student Profile and Rahmatan Lil Alamin Student Profile Strengthening Project in Madrasah - Ani Zahrotun Nisa'; Hakiman Hakiman; Aminuddin Aminuddin (JENIUS (Journal of Education Policy and Elementary Education Issues), 2025)
The study aims to explore the implementation of the Strengthening Pancasila Student Profile and Rahmatan lil Alamin Student Profile Project (P5PPRA) in introducing healthy food in Islamic schools (madrasah). The research employed a descriptive qualitative method with data collected through observation, in-depth interviews, and documentation studies. The research subjects consisted of the project coordinator and facilitator team, while the informants were the school principal, guidance and counseling teacher, and other teachers. Data were analyzed using the Miles & Huberman interactive model, and data validity was ensured through source, method, and theory triangulation. The findings reveal that the P5PPRA project carried the theme “Build the Soul and Body” through activities introducing healthy food, implemented in five stages: introduction (seminar on healthy food), contextualization (visits to tofu and bread production centers), action (preparing healthy food and drinks), reflection (healthy food bazaar and self-assessment), and follow-up (exhibition of works). The project had a positive impact, as students gained a deeper understanding of the importance of healthy food and its relation to health and intelligence.